2017
DOI: 10.1113/ep086370
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation decreases susceptibility of the heart to ventricular fibrillation in a canine model of chronic kidney disease

Abstract: What is the central question of this study? Renal denervation (RDN) has been shown to be effective and safe, resulting in better control of blood pressure and an improvement in left ventricular hypertrophy in chronic kidney disease (CKD) patients. Ventricular arrhythmias and sudden cardiac death are common causes of death in CKD patients, but previous studies pay almost no attention to the effects of RDN on the risk of ventricular fibrillation associated with CKD. What is the main finding and its importance? R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…33,34 Additionally, animal experiments reported that CKD could lead to increasing vulnerability to lethal ventricular arrhythmia. 35,36 Similarly, the results for Group 3, who had a higher eGFR value than that in other groups, found that the proportion of ROSC at hospital arrival was high. Therefore, it might be reasoned that the patients in Groups 1 or 2 would have a high possibility of reoccurrence or sustaining of the VF, even if defibrillation were performed, and that they would have poor neurological outcomes.…”
Section: Discussionmentioning
confidence: 84%
“…33,34 Additionally, animal experiments reported that CKD could lead to increasing vulnerability to lethal ventricular arrhythmia. 35,36 Similarly, the results for Group 3, who had a higher eGFR value than that in other groups, found that the proportion of ROSC at hospital arrival was high. Therefore, it might be reasoned that the patients in Groups 1 or 2 would have a high possibility of reoccurrence or sustaining of the VF, even if defibrillation were performed, and that they would have poor neurological outcomes.…”
Section: Discussionmentioning
confidence: 84%
“…Of course, there are also models for electrical heart disease without induction of heart failure. Dogs with drug‐induced long QT syndrome (LQTS) and kidney disease achieved by renal infarction are highly inducible for ventricular arrhythmias by pacing protocols or sympathetic challenge (Gallacher et al, 2007 ; Levine et al, 1985 ; Tang et al, 2017 ). LQTS and kidney disease are also well‐known clinical conditions that predispose the occurrence of ventricular arrhythmias.…”
Section: Canine Models In Cardiovascular Researchmentioning
confidence: 99%
“…Similar findings were reported with experimental hypertension in mice [ 52 ]. In addition, Tang and co-workers recently reported an increased risk of ventricular fibrillation in dogs with CKD, which was attenuated by renal denervation [ 53 ]. These results were attributed to reduced left ventricle (LV) hypertrophy, sympathetic activation, and inflammation.…”
Section: Kidney Pathologymentioning
confidence: 99%